Design and application of radio frequency identification systems - Uddin, Md. Jasim; Ibrahimy, Muhammad Ibn; Reaz, Mamun Ibn; Nordin, Anis Nurashikin (EuroJournals Publishing, Inc., 2009)
The recent world, development of effective technologies for linking the object wireless information is being prompted in various fields. Radio frequency identification (RFID) is the latest technology for automatic identification which allows the transmission of a unique serial number wirelessly. The purpose of this paper is to review RFID systems and its various components infrastructure. The components and features are still under research and being integrated in existing systems to create a marketable and potential new system. To achieve higher performance; low cost, low power RFID tag with efficient anticollision technique which provides a large throughput and flexible security mechanism is required. The review has shown different types of readers, antennas and tags which would becomes a bottleneck to reduce the RFID cost. The paper has shown details the entire components where RFID researchers will get benefit for the development of future technology. The challenges of RFID system design with the entire components (Reader, Tag and Antenna) and its advantages, disadvantages are briefly explained.